The influence of sports on the development of self-esteem in disabled athletes who have achieved championships: a descriptive study - Prima Aulia; Dwi Puspasari; Nurul Huda; Rahma Kamandasari (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2025)
Introduction: Self-esteem is an essential psychological factor for athletes with disabilities, especially those who have achieved success in sports competitions.